Human Fertility Methods and Protocols - Rosenwaks, Zev.; Rosenwaks, Zev.; Wassarman, Paul M.; Wassarman, Paul M. (Methods in Molecular Biology,, 2014)
Human Fertility: Methods and Protocols is intended for all practitioners of reproductive medicine and ART, as well as for embryologists and reproductive, developmental, cell, and molecular biologists, and others in the biomedical sciences. The volume presents straight-forward manner best practice approaches for overcoming a host of fertility challenges.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.     Authoritative and cutting-edge, Human Fertility: Methods and Protocols aids scientists in continuing to study assisted reproductive technologies.